(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article examines the improvement of strategic management mechanisms for service sector enterprises in the context of digital transformation. The relevance of the topic is determined by the growing influence of digital technologies on managerial decision-making, customer relations, business process organization, and the long-term competitiveness of service companies. The study is based on the idea that digital transformation should not be interpreted only as the introduction of new technologies, but as a comprehensive managerial change affecting strategic priorities, organizational structure, resource allocation, and performance control systems. Particular attention is given to the adaptation of strategic management tools to the changing conditions of the digital economy, where speed, flexibility, data-driven decisions, and customercentered approaches become decisive factors of sustainable development. The article analyzes the main directions for improving strategic management mechanisms in service enterprises, including the integration of digital platforms into management practice, the strengthening of analytical support for strategic planning, the modernization of organizational coordination, and the development of adaptive models of competitive behavior. It is substantiated that the effectiveness of strategic management in the service sector increasingly depends on the ability of enterprises to combine technological modernization with managerial innovation. The research also highlights the importance of digital competencies, strategic monitoring, and the use of integrated information systems for increasing managerial efficiency. As a result, the paper proposes a conceptual approach to improving strategic management mechanisms that can enhance the resilience, responsiveness, and market sustainability of service sector enterprises under conditions of rapid digital change.